Infertility around the globe: new thinking on gender, reproductive technologies and global movements in the 21st century - Inhorn, Marcia C; Patrizio, Pasquale (Human reproduction update, 2015)
Infertility is estimated to affect as many as 186 million people worldwide. Although male infertility contributes to more than half of all cases of global childlessness, infertility remains a woman's social burden. Unfortunately, areas of the world with the highest rates of infertility are often those with poor access to assisted reproductive techniques (ARTs). In such settings, women may be abandoned to their childless destinies. However, emerging data suggest that making ART accessible and affordable is an important gender intervention. To that end, this article presents an overview of what we know about global infertility, ART and changing gender relations, posing five key questions: (i) why is infertility an ongoing global reproductive health problem? (ii) What are the gender effects of infertility, and are they changing over time? (iii) What do we know about the globalization of ART to resource-poor settings? (iv) How are new global initiatives attempting to improve access to IVF? (v) Finally, what can be done to overcome infertility, help the infertile and enhance low-cost IVF (LCIVF) activism? An exhaustive literature review using MEDLINE, Google Scholar and the keyword search function provided through the Yale University Library (i.e. which scans multiple databases simultaneously) identified 103 peer-reviewed journal articles and 37 monographs, chapters and reports from the years 2000-2014 in the areas of: (i) infertility demography, (ii) ART in low-resource settings, (iii) gender and infertility in low-resource settings and (iv) the rise of LCIVF initiatives. International Federation of Fertility Societies Surveillance reports were particularly helpful in identifying important global trends in IVF clinic distribution between 2002 and 2010. Additionally, a series of articles published by scholars who are tracking global cross-border reproductive care (CBRC) trends, as well as others who are involved in the growing LCIVF movement, were invaluable. Recent global demographic surveys indicate that infertility remains an ongoing reproductive problem, with six key demographic features. Despite the massive global expansion of ART services over the past decade (2005-2015), ART remains inaccessible in many parts of the world, particularly in sub-Saharan Africa, where IVF clinics are still absent in most countries. For women living in such ART-poor settings, the gender effects of infertility may be devastating. In contrast, in ART-rich regions such as the Middle East, the negative gender effects of infertility are diminishing over time, especially with state subsidization of ART. Furthermore, men are increasingly acknowledging their male infertility and seeking ICSI. Thus, access to ART may ameliorate gender discrimination, especially in the Global South. To that end, a number of clinician-led, LCIVF initiatives are in development to provide affordable ART, particularly in Africa. Without access to LCIVF, many infertile couples must incur catastrophic expenditures to fund their IVF, or engage in CBRC to seek lower-cost IVF elsewhere. Given the present realities, three future directions for research and intervention are suggested: (i) address the preventable causes of infertility, (ii) provide support and alternatives for the infertile and (iii) encourage new LCIVF initiatives to improve availability, affordability and acceptability of ART around the globe.